Microcrédito e microfinanças: análise do perfil do cliente do programa crediamigo em Mossoró- RN - Silva, Anna Isabele dos Santos (Universidade Federal Rural do Semi-Árido, 2021)
The number of workers and businesses in the informal sector has increased as a result of the economic crises that Brazil has gone through. Thus, in the 1990s, the country began a movement to reorganize the banking system, in order to integrate the low-income population, through the creation of products such as oriented productive microcredit, like as Banco do Nordeste's Crediamigo Program. So, the present work aims to analyze the profile of the Crediamigo Program client in the city of Mossoró-RN. Therefore, a case study was carried out, based on fieldwork with a portion of the customers of the Crediamigo Mossoró unit. This is a qualitative and exploratory research, using bibliographic and documentary methods and application of questionnaires, in which it was possible to trace the profile of these microentrepreneurs and, alternatively, understand their perspective on the impact of the program on their microbusiness. The study found that, in the share of clients participating in the survey, the majority are female, and their activity is informal, reflecting the data indicated in the national reports of Banco do Nordeste
Keywords: Microcrédito; Programa Crediamigo; Microcrédito Produtivo Orientado; Perfil Socioeconômico; Microcredit; Crediamigo Program; Oriented Productive Microcredit; Socioeconomic Profile; ENGENHARIAS::ENGENHARIA DE PRODUCAO